The Legality of Debt Agreement Via Whatsapp Messages - wildan arif; Suci Kamilah; Renaldy Afriyanto (Jurnal Jurisprudence, 2021)
Objective: This paper analyzes and studies the legal power of debt agreements through WhatsApp messagesMethodology: This research methods was juridical normative to analyze constitutional regulations or other legal sources that concern the legal basis of agreements. It uses a practical approachResults: The results showed that the debt agreement has fulfilled the required elements to make an agreement valid. It is a type of written agreement; thus, it can become written legal evidence in civil law trials in IndonesiaPurpose: The chat messages via WhatsApp indicate the creation of debt may become a piece of evidence in court. It is categorized as evidence of a written agreement. There are five kinds of evidencing instruments according to civil law procedures in Article HIR/284 RBG that is amended into Article 1866 of the Civil Law, namely written evidence, witness evidence, presupposition, confession, and oath. Thus, in the case of the debt agreement via WhatsApp messages, that message is categorized as a written agreement. It must be printed and legalized according to the legal stipulations.WhatsApp is a social media application. Thus, it is categorized as a shred of evidence in court according to Article 5 clause (1) of the Law No. 11 of 2008 on Electronic Information and Transaction as changed into the Law No. 19 of 2016 on the Change of the Law No. 11 of 2008 on Electronic Information and Transaction.Novelty/Originality: The debt agreement via application whatsap was categorized a new legal event. The most significant novelty value from the results of this research is the legal status of new debt agreement methods, namely the debt agreements through WhatsApp messages. Whatsapp was a social media. the agreement through the WhatsApp messages is legally valid so long as it fulfills the requirements of an agreement as stipulated in Article 1320 BW and that the agreement is categorized as a written agreement. Thus, it contains legal consequences if a party violates that agreement. This agreement is still valid even without a piece of evidence in the form of an authentic letter, as an authentic letter is a deed letter that can be divided into an authentic deed (Authentiek) and underhand deed (Onderhands).